Small and medium-sized manufacturing enterprises in Latin America and the Caribbean under the new economic model - Peres, Wilson (2000)
Describes the performance of small and medium-sized manufacturing enterprises (SMEs) in 10 Latin American countries under the New Economic Model (NEM). Analyzes SME performance in relation to production, employment and productivity and in comparison to larger enterprises.